To Know Where He Lies : DNA Technology and the Search for Srebrenica's Missing. - Wagner, Sarah E., 1972- (University of California Press, 2008)
In the aftermath of the 1992-1995 Bosnian war, the discovery of unmarked mass graves revealed Europe's worst atrocity since World War II: the genocide in the UN "safe area" of Srebrenica. To Know Where He Lies provides a powerful account of the innovative genetic technology developed to identify the eight thousand Bosnian Muslim (Bosniak) men and boys found in those graves and elsewhere, demonstrating how memory, imagination, and science come together to recover identities lost to genocide. Sarah E. Wagner explores technology's import across several areas of postwar Bosnian society--for familie.